Analysis Of Research Works On The Design And Production Of Antistatic Special Clothing - Sheraliyeva Risolatxon Islombek qizi (Zien Journals, 2025)
This article presents an analysis of research works in the field of design, quality production and use of antistatic special clothing.
Keywords: Antistatic special clothing; radiation exposure; electropower